TEACHER STRATEGIES IN MANAGING STUDENTS' DIGITAL PREFERENCES TO STRENGTHEN AL-QURAN LITERACY - Yeti Nurdiningsih; Devi Sulaeman; Mia Audina Musyadad; Dedeh Kurniasih; Asep Supriatna (JCI Publisher, 2026)
The development of digital technology has influenced the learning preferences of students at the elementary level, including in the context of Islamic education. Intensive use of gadgets presents both challenges and opportunities in strengthening Quranic literacy. This study aims to analyze and describe teachers' strategies in managing students' digital preferences to strengthen Quranic literacy at Madrasah Ibtidaiyah Nurul Falah Majalaya - Karawang. The study used a qualitative approach with a case study type. Data were collected through participatory observation, in-depth interviews, and documentation studies, then analyzed interactively through data reduction, data presentation, and drawing conclusions. The results show that teachers' strategies are implemented through three main approaches: digital media integration in Quranic learning, literacy habits based on school culture, and collaboration with parents in supervising gadget use. Teachers direct the use of Quranic applications and audio-visual media in a controlled manner so that students' digital preferences are shifted to educational activities. The culture of morning literacy and intensive communication with parents strengthens the continuity of strategies at school and at home. The implications of this research emphasize the importance of redefining the role of teachers as adaptive and contextual managers of digital preferences in Islamic education. These findings contribute to the development of Qur'anic pedagogical practices that are responsive to the dynamics of the digital era.